Black esophagus - Uyar, Seyit; Duman, Adil; Tan, Ayşe; Akbay Harmandar, Ferda; İnal, Gülşah and Köker, Gökhan and Şahintürk, Yasin and Bostan, Feyzi and Çekin, Ayhan Hilmi (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Uyar S, Duman A, Tan A, et al. Black esophagus. Turk J Gastroenterol 2019; 30(11): 986-7.